Evaluasi Kualitas Nutrien Hydroponic Corn Green Fodder Jagung Putih Sebagai Pakan Ternak Pada Umur Panen Yang Berbeda - Happy Rizqa Amaliah; Ali Bain; Widhi Kurniawan (Jurnal Ilmiah Peternakan Halu Oleo, 2024)
This study aims to evaluate the effect of differences in harvest age on the characteristics of fodder of corn plants that are maintained hydroponically. This research will be carried out using a completely randomized design (CRD) with 5 treatments and 4 replications, so that the experimental units used are 20 units to get a good harvest time. The treatments used in this study were P1 (Hydroponic growing media at harvesting age of 7 days), P2 (Hydroponic growing media at harvesting age of 9 days), P3 (Hydroponic growing media at harvesting age 11 days), P4 (Hydroponic growing media at harvesting age 13 days), P5 (Hydroponic growing media, harvesting age 15 days). The parameters evaluated were (a) dry weight (BK), (b) organic weight (BO), (c)crude protein content (PK), (d) crude fiber content (SK) and (e) crude fat content (LK). The results revealed that the average dry matter ranged from 12.98–6.27%, while the average organic weight ranged from 96.90–93.52%, the protein content ranged from 23.30–10.14%, the crude fiber content ranged from 2.65–20.28%, and the results of crude fat content ranged from 2.65–2.86%.Based on the results of the study, it can be concluded that hydroponic corn green fodder white corn with different harvest ages can have a significant effect on the production of dry matter, organic matter, crude protein and crude fiber. The best harvest was found in the P1 treatment, namely at 7 days of harvest it was able to produce 23% crude protein content. The longest harvest age (15 days) resulted in the lowest dry matter, organic matter and crude protein content and the highest crude fiber content.